Self-Concept and Self-Efficacy Beliefs as Determinants of Success among Equality Non-Formal Education Learners - Kamilin Kamilin; Muhadjir Effendy; Rosyid Al Atok; Ach. Rasyad (Journal of General Education and Humanities, 2026)
Background: Successful implementation of non-formal equality education requires learning centers to produce competent and independent learners. Gap: While much attention has been given to external factors and correcting educational weaknesses, there is a critical need to understand how internal self-constructs actively build learner competencies. Method: Therefore, the present study aims to explain the specific determinants of learner success by examining self-concept and self-efficacy beliefs. A qualitative phenomenological design was employed, utilizing in-depth, semi-structured interviews. Participants: Participants included adult learners such as farmers, industrial workers, and previous school dropouts enrolled in the vocational Package C (high school equivalence) program at Community Learning Centers (CLCs) in Malang District. Findings: Thematic content analysis revealed that successful learner development is rooted in distinct self-concept components, including self-image, idealism, and study-orientation. Additionally, self-efficacy manifests concretely through learners' ability to complete tasks, manage time, and respond positively to tutors' verbal persuasion. Implications & Contribution: Rather than merely identifying a broad "positive subjective experience," this study demonstrates how these internal constructs directly translate into tangible academic readiness, enhanced motivation, and the mastery of practical life skills. The primary contribution of this research is providing a targeted framework for CLCs to integrate tailored guidance and counseling services, ultimately leveraging learners' self-constructs to foster economic welfare and long-term social independence.